Trauma in First Person : Diary Writing During the Holocaust - Goldberg, Amos (Book collections on Project MUSE., 2017)
What are the effects of radical oppression on the human psyche? What happens to the inner self of the powerless and traumatized victim, especially during times of widespread horror? In this bold and deeply penetrating book, Amos Goldberg addresses diary writing by Jews under Nazi persecution. Throughout Europe, in towns, villages, ghettos, forests, hideouts, concentration and labor camps, and even in extermination camps, Jews of all ages and of all cultural backgrounds described in writing what befell them. Goldberg claims that diary and memoir writing was perhaps the most important literary g.